A Polymorphic (CT)n-SSR Influences the Activity of the Litopenaeus vannamei IRF Gene Implicated in Viral Resistance - Yin, Bin; Wang, Haiyang; Zhu, Peng; Weng, Shaoping; He, Jianguo; Li, Chaozheng (Frontiers in Genetics, 2019)
Simple sequence repeats (SSRs) of short nucleotide motifs occur very frequently in the 5′ untranslated coding region (5′-UTR) of genes and have been implicated in the regulation of gene expression. In this study, we identified an SSR with a variable number of CT repeats in the 5′-UTR of the Litopenaeus vannamei IRF (LvIRF) gene that has been shown to mediate antiviral responses by inducing the expression of Vago, a functional homolog of mammalian IFN. We then explored the effects of varying the number of (CT)n repeats on the expression of LvIRF using both dual-luciferase reporter assays and Western blots. Our results demonstrate that the length of the (CT)n-SSR in this gene can influence the expressional level of LvIRF, in that a shorter (CT)n repeat had a stronger ability to induce the expression of LvIRF. Moreover, we found that the (CT)n repeat in LvIRF was associated with viral resistance in shrimp. Individual shrimps with shorter (CT)n repeats in the 5′-UTR of LvIRF exhibited high tolerance to white spot syndrome virus (WSSV), and this trait was inherited in offspring. Taken together, these results indicated that this (CT)n-SSR could be used as a molecular marker for shrimp breeding for WSSV resistance.